STUDI KUALITAS AIR TANAH UNTUK KEBUTUHAN AIR MINUM DI KELURAHAN TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Andre Hanusa Hanusa; no Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The objectives of this study were: (1) To determine the quality of ground water for drinking water needs in Talang Mandi Subdistrict, Mandau District, Bengkalis Regency, (2) To determine the community's efforts in meeting the needs of brsih water. The type of this research is Mixed Methods, Population and sample: (1) Groundwater sample of farmer formation (Tup) and Minas formation (Qpmi), (2) Talang Mandi Village Community. The sampling method is purposive sampling by taking one water sample from the farmer formation (Tup) and the minas formation (Qpmi) in Talang Mandi Village. The technique of collecting data is by taking a sample of groundwater from the farmer formation (Tup) and Minas formation (Qpmi), interview and documentation. Data analysis used two approaches, namely a quantitative approach and a qualitative approach. The results of this study are (1) the quality of groundwater in the physical parameters of farmer formation (Tup) and mineral formation (Qpmi) in Talang Mandi Village, Mandau District, Bengkalis Regency including color, smell and taste, does not meet the standards of PERMENKES No.492/2010 concerning quality requirements. drinking water. In the chemical parameters of each farmer formation and mineral formations include pH, iron (fe), copper (Cu) and zinc (Zn), which in farmer formations the pH level has not met the standards of PERMENKES No.492/2010 concerning drinking water quality requirements. (2) The community's efforts to meet the needs of clean water are by taking water at the PT.Chevron Pacific Indonesia location, buying tank water and collecting rainwater.